DAMPAK INFRASTRUKTUR TERHADAP SOSIAL EKONOMI DAN PENDIDIKAN DI KAMPUNG JAYA MAKMUR DAN ANUMBOB DISTRIK KURIK - Roisyah Budiati; Lailatul Firda Saputri; Irkham Ibra Maulana; Yonarlianto Tembang; Umar Yampap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Road infrastructure is a link between regions in Kurik District. However, due to several factors the road is damaged. The purpose of the study Describe the impact of road infrastructure on social, economic and educational conditions in the Jaya Makmur and Anumbob villages of Kurik District. The type of research is qualitative. Data collection techniques interviews, observations, and questionnaires or a combination of the three are Triangulation. Analysis techniques are data reduction, data presentation, and conclusions. The sampling technique is purposive sampling. The number of samples is 60 people. The results of the study The impact of road infrastructure on social conditions is that it hinders people from carrying out mobility during important moments such as the fasting month and Eid al-Fitr. However, on the other hand, the community has a very high value of mutual cooperation, namely for the initiative to repair roads independently by filling the road with excavated soil. While the impact of road infrastructure on economic conditions is hampering the distribution of agricultural products considering that most people earn a living as farmers, and the impact of infrastructure in the field of education is affecting the number of teacher and student attendance, as well as affecting the psychological state of students